Introduction : 10 ans, mais encore ? De l’actualité des études urbaines et de Métropoles - Stéphane Cadiou; Julie Pollard (Métropoles)
This introduction presents the structuring of this special issue around four axes. The first set of articles locates the trajectory of Métropoles with regards to the evolution of its ambitions and contents, as well as editorial context. The second set of articles brings together scientific investigations, which collectively question the conditions of criticism in urban studies. The third part focuses on the issue of metropolization in cities in the South, exploring areas that have not yet been adequately covered in the journal. Finally, several portraits close this special issue. They invite the reader to reconsider disciplinary boundaries and interfaces between social and political worlds.